Is an extension of the safe zone possible without jeopardizing the proximal radioulnar joint when performing a radial head plate osteosynthesis? - Ries, Christian; Pfau, Doreen (Journal of shoulder and elbow surgery, 2015)
Background: Proximal radial fractures are common elbow injuries. Because of the fracture pattern, stability criteria, or plate configuration, a plate position outside the “safe zone” (SZ) may be required in some cases when performing a radial head plate osteosynthesis. We examined the gross anatomy of the radial head and analyzed different so-called low-profile and precontoured radial head and neck plates with respect to the SZ. Materials and methods: Macroscopic measurements of the radial head and neck of 22 formalin-fixed human cadaveric upper extremities were obtained. The SZ was determined by maximum forearm rotation. If the edge of a plate could be extended beyond the respective SZ boundary without jeopardizing the proximal radioulnar joint (PRUJ) in maximum forearm rotation, a new plate-specific SZ boundary was set. Results: The mean SZ was 133° (SD, 14°). Among the 5 plates studied, only the 2 radial neck designs allowed the anterior edge of the plate to partially pass the lesser sigmoid notch of the ulna and consequently afforded a significant extension of the SZ in maximum pronation. All 3 radial head designs had to remain within the SZ to avoid interference with the PRUJ. A safe plate position depends on individual plate dimensions, particularly the proximal plate width, and the diameter of the radial head. The smaller the head diameter, the more accurately a plate must be placed within the SZ. Conclusions: If an extension of the SZ in radial head plate osteosynthesis is not essential, we recommend respecting the SZ to minimize the possibility of interference with the PRUJ.